Multinational Companies and their Impact on Creating Economic Crises in Developing Countries - عبد الحفيظ محمد حمد, خالد (Finance and Business Economies Review, 2020)
The research aimed to explain the social, administrative, political and technical impacts of multinationals on developing countries. And identify some economic threats resulting from the activity of these companies and explain their impact in creating economic crises with a view to reaching results around them. The research adopted the use of the historical approach, in addition to the descriptive approach. This study came to a number of conclusions, the most important of which is: These multi- national companies are influenced by a number of variables such as technological, demographic, economic and social variables. These companies go into business with developing countries according to their specific characteristics. The study concluded to some directives to developing countries. The first priority for investment is local savings. Foreign investment should be directed to productive sectors and not to consumer or services sectors.